THE INFLUENCE OF KNOWLEDGE MANAGEMENT ON WORK-LIFE BALANCE MEDIATED BY CO-WORKER SUPPORT - Pinandang Nainggolan; Syaifuddin Syaifuddin; Fajar Rezeki Ananda Lubis (Yayasan Nuraini Ibrahim Mandiri, 2026)
This study aims to analyze the factors that influence Work-Life Balance (WLB) among employees at the Bhayangkara Level II Hospital in Medan. The variables studied include Knowledge Management as the independent variable, Work-Life Balance as the dependent variable, and Co-Worker Support as the moderator variable. The research method used is a quantitative approach with moderated regression analysis techniques. Data were collected through questionnaires from respondents who are hospital employees, both medical and non-medical personnel. The results of the study indicate that Knowledge Management has a significant effect on Work-Life Balance. Likewise, it was found that Co-Worker Support was proven to significantly moderate the effect of Knowledge Management on Work-Life Balance. These findings indicate the importance of strengthening knowledge management and organizational support in establishing work-life balance, as well as the need for a more effective approach in building support among colleagues.